2018
DOI: 10.1002/cae.22022
|View full text |Cite
|
Sign up to set email alerts
|

TDEG based framework and tools for innovation in teaching technical drawing: The example of LaMoo project

Abstract: This work presents the development of an integrated framework and related tools for innovation and improvement in the teaching of Technical Drawing. This framework is based on the “Technical Drawing Evaluation Grid—TDEG.” This grid is currently used, by the authors, for the definition and the development of different kinds of tools for supporting both teaching and learning and for the evaluation of Technical Drawing and engineering graphics topics knowledge in general. In particular, this paper focuses on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The ever-increasing number of new software/Add-Ins available for Moodle is indicative of the interest of software developers and researchers to improve the useability of Moodle for online teaching and education. Course developers utilise plug-ins to assist with automatic essay marking, randomising questions, and identifying ineffective questions (Koneru, 2017 ; Schweighofer et al, 2019 ; Villa et al, 2018 ). Table 7 lists several software applications that can be integrated into LMSs and, in particular, Moodle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ever-increasing number of new software/Add-Ins available for Moodle is indicative of the interest of software developers and researchers to improve the useability of Moodle for online teaching and education. Course developers utilise plug-ins to assist with automatic essay marking, randomising questions, and identifying ineffective questions (Koneru, 2017 ; Schweighofer et al, 2019 ; Villa et al, 2018 ). Table 7 lists several software applications that can be integrated into LMSs and, in particular, Moodle.…”
Section: Resultsmentioning
confidence: 99%
“…Marking and feedback Four percent of reviewed articles focused on improving and streamlining the marking and feedback processes for both students and teachers. These Page 14 of 24 Gamage et al International Journal of STEM Education (2022) 9:9 studies indicate that online marking systems associated with Moodle lower the long-term costs, increase the speed of providing feedback, provide greater flexibility with respect to location and timing and reduce the space required to manage the assessment process (García López & García Mazarío, 2016;Koneru, 2017;Villa et al, 2018). A study with 57 academics conducted at Monash University, Australia, highlighted Moodle's reliability, and improved impartiality of the assessment process (George-Williams et al, 2019).…”
Section: Theme 4: Assessmentmentioning
confidence: 99%
“…However, in the educational fields of technical and engineering drawing, our results are in agreement with those found in the literature (Ayala-Alvarez et al 2017), since, in a 5-point Likert scale, the respondents showed a high mean score (M = 3.80; SD = 1.14) regarding the innovative resource's usefulness. According to Villa et al (2018), students tend to have difficulties in understanding the 3D shape of objects starting from their two-dimensional representations, concerning their spatial vision. However, in this study, the mean score of the participants about their own assessment of spatial vision was as follows: 3.00 (SD = 1.08) for masters' degree students, 3.22 (SD = 1.09) for undergraduate students and 2.70 (SD = 0.98) for tutorial students.…”
Section: Discussionmentioning
confidence: 99%
“…This work is part of a research aimed at improving teaching and learning of technical drawing (TD) for BS courses in Engineering. As mentioned in previous works [1][2][3][4][5], the Universities of Brescia, Udine and Cassino and Southern Lazio have been collaborating on these themes since 2014. In this paper, the authors analyze the results of questionnaires proposed to first years students in Industrial or Mechanical Engineering during the academic year 2016-2017.…”
Section: Introductionmentioning
confidence: 91%